2022
DOI: 10.33222/juara.v7i2.1496
|View full text |Cite
|
Sign up to set email alerts
|

Badminton Court Agility Test

Abstract: In 2016 PP PBSI published a book of criteria and physical parameters for athletes entering national training and version 1 for athletes. There is an agility test called the agility court. However, this agility court test does not yet have the validity and reliability values ​​needed for a trial, so it still needs to be tested for validity and reliability. This study aims to reveal the truth and reliability of the badminton game agility court test in athletes aged from children to Adolescents. This research use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It was then discovered that the agility test model was Y-shaped with variations in path or slope angle Alim et al, 2024). In the age classification, search results found that the beginning of a career in badminton starts from the age of 15 (Williyanto et al, 2021); (Kusnadi et al, 2022); (Rodríguez et al, 2022). The result of the first step is to set the Y agility test for badminton athletes aged 15-17 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then discovered that the agility test model was Y-shaped with variations in path or slope angle Alim et al, 2024). In the age classification, search results found that the beginning of a career in badminton starts from the age of 15 (Williyanto et al, 2021); (Kusnadi et al, 2022); (Rodríguez et al, 2022). The result of the first step is to set the Y agility test for badminton athletes aged 15-17 years.…”
Section: Methodsmentioning
confidence: 99%
“…In Indonesia, badminton has been taught to children, and then it has been carried out to foster talented teenager athletes or special badminton schools from the age of 12 (Hasyim & Hasanuddin, 2023); (Wijayanti et al, 2024); Mandan et al, 2024) . In looking for coaching talented athletes or special badminton schools, there is a stage that must be passed by conducting physical fitness tests, basic biomotor ability tests, anthrophometric tests, and badminton skill tests ( (Edmizal & Soniawan, 2019); (Phomsoupha & Laffaye, 2020); (Williyanto et al, 2021); (Kusnadi et al, 2022). However, the tests carried out for athletes are still limited to general tests or not yet specific to badminton.…”
Section: Introductionmentioning
confidence: 99%